2012
DOI: 10.4040/jkan.2012.42.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Breast Feeding Rates and Factors Influencing Breast Feeding Practice in Late Preterm Infants: Comparison with Preterm Born at Less than 34 Weeks of Gestational Age

Abstract: Purpose: This study was done to compare breast feeding rates and factors influencing feeding practice between late preterm (34≤ GA< 37) and preterm infants (GA< 34). Methods: A survey was done of 207 late preterm and 117 preterm infants in neonatal intensive care units (NICU) of 4 university hospitals in D city. Data were collected from July 2009 to June 2010 from 324 medical records in the NICU. Breast-feeding at home was checked either by telephone survey or questioning during hospital visits. Results: Rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
4
15
0
2
Order By: Relevance
“…Despite the risks associated with prematurity, these infants are often managed in postnatal units instead of special units with qualified health-care professionals assigned to LPI care during the immediate postpartum recovery period following birth (Engle et al, 2007;Phillips et al, 2013). A lower breast-feeding prevalence has been reported for LPIs in comparison with term infants (Demirci et al, 2013) and preterm infants born at less than 34 weeks of GA (Jang et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Despite the risks associated with prematurity, these infants are often managed in postnatal units instead of special units with qualified health-care professionals assigned to LPI care during the immediate postpartum recovery period following birth (Engle et al, 2007;Phillips et al, 2013). A lower breast-feeding prevalence has been reported for LPIs in comparison with term infants (Demirci et al, 2013) and preterm infants born at less than 34 weeks of GA (Jang et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Given the known short‐ and long‐term consequences of LPT births and the maternal and infant health benefits of breastfeeding (Victora et al, ), it is a concern that several studies have reported lower rates of breastfeeding initiation and a shorter duration of breastfeeding in LPT infants not only compared with term infants (Ayton, Hansen, Quinn, & Nelson, ; Demirci, Sereika, & Bogen, ; Donath & Amir, ; Goyal, Attanasio, & Kozhimannil, ; Hackman, Alligood‐Percoco, Martin, Zhu, & Kjerulff, ; Rayfield, Oakley, & Quigley, ), but also compared with more preterm infants (Jang, Lee, & Kim, ). There are numerous possible reasons for these differences in breastfeeding, for example, maternal health problems, delayed maternal lactogenesis, infants' medical problems, and immaturity.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Previous studies have shown that breastfeeding rates among late preterm infants (ie, those born at 34-36 6/7 weeks' gestation) are lower than rates among earlier preterm infants. [5][6][7][8] Very premature infants are at a higher risk of several morbidities, including necrotizing enterocolitis; it is thus possible that health care providers are more motivated to ensure early breast milk feeding for these infants. Some late preterm infants are otherwise healthy at birth and receive their newborn care in the well nursery, whereas others require neonatal intensive care due to hypothermia, hypoglycemia, respiratory support, infection, feeding difficulties, or other medical problems.…”
mentioning
confidence: 99%